Urban Regulation of the Development of the Federal Territory - V. A. Mayboroda (Теоретическая и прикладная юриспруденция)
The article formulated an idea of the possibilities of urban planning regulation in order to develop a new territorial and legal education in the Russian Federation — the federal territory. The concentration of all public powers at the federal level implies the need to strike a different balance of regulation in the exercise of local government powers in relation to urban planning regulation.